Огненное порубежье: [роман] / Эдуард Зорин - Зорин Эдуард Павлович (У истоков Руси, 2021)
Экземпляры: ЦБ (20230529) / Инвентарный номер: 60001 / Цена: 526.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: З-86 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44